2017
DOI: 10.5205/1981-8963-v11i12a25152p5129-5138-2017
|View full text |Cite
|
Sign up to set email alerts
|

Cuidado ao lactente para mães em consultas de puericultura: intervenção em sala de espera

Abstract: Objective: to report the experience of educational sessions for mothers about infant care in a waiting room for child care consultations. Method: qualitative, descriptive study, type of experience report, in which the educational sessions took place in a Primary Health Care Unit, whose data collection occurred from August 2015 to March 2017. Results: six educational sessions were carried out verifying the pre-knowledge -existing, implementing health education strategies and, later, verifying knowledge. We high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
2
0
2
Order By: Relevance
“…No que se ref ere à amamentação, a maioria dos problemas relacionados à lactação pode ser prevenida com esvaziamento adequado das mamas e, quando presentes deve-se obter o manejo adequado evitandose, assim, o desmame precoce decorrente de situações dolorosas e, eventualmente, debilitantes para a nutriz (GIUGLIANI ERJ, 2014; BERNARDO FMDS, et al, 2017).…”
Section: Discussionunclassified
“…No que se ref ere à amamentação, a maioria dos problemas relacionados à lactação pode ser prevenida com esvaziamento adequado das mamas e, quando presentes deve-se obter o manejo adequado evitandose, assim, o desmame precoce decorrente de situações dolorosas e, eventualmente, debilitantes para a nutriz (GIUGLIANI ERJ, 2014; BERNARDO FMDS, et al, 2017).…”
Section: Discussionunclassified
“…In view of the need for information related to the swallowing disorder of these children, this study addressed the essential care at the moment of feeding and in administrating food by tubes through an educational intervention in order to avoid bronchoaspiration of the food. Another study which reported an educational experience in promoting infant care stated that it is important to pay special attention to the nutritional health of a child to avoid complications in their development and growth (17) . Therefore, guidance and training caregivers in relation to the feeding care of a child using tubes is extremely important, since this procedure requires the necessary minimum knowledge involving administration of diets, cleaning tubes and stomas to be done at home (18) .…”
Section: Discussionmentioning
confidence: 99%
“…Doubts can also be resolved / solved and information assimilated gains a potential for dissemination not only within the family space, but also in the community where the family establishes its social relations with other people. 18 In group consultations, according to participants' reports, families are clarified regarding the most frequent health problems that affect children according to age and also the expected behavioral traits according to developmental milestones.…”
Section: Discussionmentioning
confidence: 99%